Biomechanics of rugby place kicking - Atack, A. (2016)
Approximately 45% of the points scored in international Rugby Union matches are the result of place kicks (Quarrie & Hopkins, 2015). However, the key technique characteristics underpinning this skill are not well understood. The aim of this thesis was therefore to investigate rugby place kicking technique and performance, and understand how these differ between successful and less successful place kickers. In order to objectively quantify place kick performance outcome from data collected in a laboratory environment, a novel performance measure representative of the maximum distance that any given place kick could be successful from was developed. This measure combined initial ball flight data with previously published aerodynamic forces and was shown to predict ball location with a mean error of 4.0%. Full body motion capture and ground reaction force data were then collected from 33 experienced (amateur to senior international level) kickers and three groups of kickers were identified based on their performance outcome: long, short, and wide-left kickers. Differences were observed in the initial ball flight characteristics between the three groups and specific aspects of technique were then analysed to understand how these different performance outcomes were achieved. The long and wide-left kickers used different strategies to achieve comparable forward kicking foot velocities and initial ball velocities. The wide-left kickers used a hip flexor strategy: greater positive hip flexor work which was facilitated by a stretch across the trunk at the top of the backswing, followed by longitudinal rotation throughout the downswing. In contrast, the long kickers used a knee extensor strategy: greater positive knee extensor work and a more consistent trunk orientation throughout the downswing. Although both strategies led to comparably high initial ball velocity magnitudes, the hip flexor strategy led to greater longitudinal ball spin and an initial ball velocity vector directed towards the left-hand-side. Kickers who achieve fast ball velocities but miss left could potentially benefit from technical interventions to address their trunk kinematics or development of their kicking knee extensor involvement. The long kickers achieved faster kicking foot and initial ball velocities than the short kickers. The long kickers took a more angled and faster approach to the ball compared with the short kickers. This enabled the pelvis to be less front-on at the top of the backswing, meaning that the kicking foot was further away from the ball at this point and subsequently travelled a longer path to initial ball contact. The long kickers also demonstrated greater horizontal whole-body CM deceleration between support foot contact and initial ball contact and performed greater hip flexor and knee extensor positive work than the short kickers during the downswing. Kickers who cannot generate fast ball velocities could potentially benefit from interventions to their approach direction and velocity, or from development of their kicking hip flexor and knee extensor involvement. This thesis has provided a comprehensive understanding of rugby place kicking technique and recommendations for both coaching practice and research.